A REASSESSMENT OF THE STATUS OF THREE TAXA WITHIN THE RHODODENDRON FORMOSUM COMPLEX (ERICACEAE: SUBSECT. MADDENIA) FROM NORTHEAST INDIA - Mao, A. A.; Roy, D. K.; Rushforth, K. (Edinburgh Journal of Botany, 2017)
A taxonomic investigation of the Rhododendron formosum complex in Northeast India was carried out. Both Rhododendron iteophyllum Hutch. and Rhododendron inaequale Hutch. are reinstated as distinct species using taxonomic characters based on comparing living plants. Detailed taxonomic accounts of Rhododendron formosum, R. iteophyllum and R. inaequale are provided, along with photographic illustrations.
Keywords: Maddenia; Northeast India; Rhododendron formosum complex; Rhododendron inaequale; Rhododendron iteophyllum